A Comparison of the Effectiveness of STEM Skewer Stick and Flash Card Learning Media on Students' Understanding of the Concept of Area of Plane Figures at SDN Layungsari 2 - Sandi Budiana; Ninda Rosfadhri; Shinta Prameswari; Ai Nursaadah (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Mathematics education at the elementary level often faces challenges in enhancing students' understanding of the concept of area in two-dimensional shapes. To address this issue, various learning media have been developed, including Science, Technology, Engineering, and Mathematics (STEM)-based tools like skewer sticks and flash cards. This study aims to compare the effectiveness of these two media in improving the understanding of the area of two-dimensional shapes among fifth-grade students at SDN Layungsari 2. The research employed a quantitative approach with a quasi-experimental design, involving two experimental groups: Class VA used STEM skewer sticks, while Class VB used flash cards. Data were collected through pre-test and post-test assessments of students' understanding of area concepts. The results showed that both groups experienced significant improvement, with the average post-test score of Class VA (88.93) being higher than that of Class VB (83.46). A t-test revealed a significant difference (p = 0.017) between the two groups, indicating that the STEM skewer stick method was more effective in enhancing conceptual understanding. These findings suggest that more concrete and interactive learning media, such as skewer sticks, can optimally increase student engagement and understanding in mathematics education.